Lexical semantics ande syntactic change shaping the lexicon in Tupi-Guarani languages - Baranger, Estefania; Califa, Martín Iván (., 2022)
.
Keywords: Humanidades::Lenguas y Literatura::Lingüística; Humanidades::Lenguas y Literatura::Lingüística